To calculate the sum of two squares in an expression, the a^2 + b^2 formula is used. The **a ^{2} + b^{2} formula** can be easily derived using the (a + b)

^{2}or (a - b)

^{2}formula.

- a
^{2}+ b^{2}= (a + b)^{2}- 2ab - a
^{2}+ b^{2}= (a - b)^{2}+ 2ab

Let us learn these along with a few solved examples in the upcoming sections.

## What is the a^2 + b^2 Formula?

The a^2 + b^2 formula is used to calculate the sum of two or more squares in an expression. Thus, a sum of squares formula or a^2 + b^2 formula can be expressed as:

a^{2} + b^{2} = (a +b)^{2} - 2ab (or) a^{2} + b^{2} = (a - b)^{2} + 2ab

where, a, b = arbitrary numbers.

Let a and b be the two numbers, the squares of a and b are a^{2} and b^{2}. The sum of the squares of a and b is a^{2 }plus b^{2}. We could obtain a formula using the known algebraic identity (a + b)^{2 }= a^{2} + b^{2} + 2ab. On subtracting 2ab from both the sides we can conclude that **a ^{2} + b^{2} = (a + b)^{2} - 2ab.**

Similarly, we can also prove that, **a ^{2} + b^{2} = (a - b)2 + 2ab.**

Cuemath is one of the world's leading math learning platforms that offers LIVE 1-to-1 online math classes for grades K-12. Our mission is to transform the way children learn math, to help them excel in school and competitive exams. Our expert tutors conduct 2 or more live classes per week, at a pace that matches the child's learning needs.

Great learning in high school using simple cues

Indulging in rote learning, you are likely to forget concepts. With Cuemath, you will learn visually and be surprised by the outcomes.

Book a Free Trial Class

## Example on a Square + b Square Formula

**Example 1:** Using the sum of squares formula, find the value of 5^{2} + 6^{2}?

**Solution:**

To find : value of 5^{2} + 6^{2}

Given: a = 5, b = 6

Usinga square plus b square formula Formula,

a^{2} + b^{2} = (a + b)^{2} - 2ab

5^{2} + 6^{2} = (5 + 6)^{2} - 2(5)(6)

= 121 − 2(30)

= 121 − 60

= 61

**Answer:** The value of 5^{2} + 6^{2 }is 61.

**Example 2:** Verify that the value of x^{2} + y^{2} is (x + y)^{2} - 2xy using a^{2} + b^{2 }formula.

**Solution:** To verify x^{2} + y^{2} = (x + y)^{2} - 2xy

Let us use the a square + b square formula,

a = x, b = y

Using the (a + b)^{2} formula let us expand the initial terms.

(a + b)^{2} = a^{2} + b^{2} + 2ab

Let us substitute the value of a and b as x and y

(x + y)^{2} = x^{2} + y^{2} + 2xy

On subtracting 2xy from both the sides,

x^{2} + y^{2} = (x + y)^{2} - 2xy

**Answer: Hence verified**

**Example 3:** Find the sum of the squares of 10 and 20 directly and use the a^2 + b^2 formula. Verify your answers.

**Solution: **

10^{2 }+ 20^{2 }= 100 + 400 = 500

Using the formula of a square + b square:

a^{2} + b^{2 }= (a + b)^{2} - 2ab, we get

10^{2 }+ 20^{2 }= (10 + 20)^{2} - 2 × 10 × 20

= 900^{ }- 400

= 500

Thus verified.

## FAQs on a^{2} + b^{2} Formula

### What is the Expansion of a^{2} + b^{2} Formula?

**a ^{2 }+ b^{2} formula** is known as the sum of squares formula it is read as a square plus b square. Its expansion is expressed as a

^{2}+ b

^{2 }= (a + b)

^{2}- 2ab.

**☛Also Check:** a^2-b^2 Formula

### How To Simplify Numbers Using the a^{2} + b^{2} Formula?

Let us understand the use of the a^{2} + b^{2} a^{2 }+ b^{2} formula with the help of the following example.**Example:** Find the value of 20^{2} + 30^{2} using the a^{2} + b^{2} formula.

To find: 20^{2} + 30^{2}

Let us assume that a = 20 and b = 30.

We will substitute these in the formula of the sum of squares formula that is, a^{2} + b^{2}

a^{2} + b^{2 }= (a +b)^{2} - 2ab

20^{2}+30^{2} = (20+30)^{2} - 2(20)(30)

= 2500 - 1200 = 1300**Answer:** 20^{2} + 30^{2} = 1300.

### What is the Formula of a Square + b Square in Algebra?

The a square plus b square formula is one of the important algebraic identities. It is represented by a^{2} + b^{2} and is read as a square plus b square. The (a^{2 }+ b^{2}) formula is expressed as a^{2} + b^{2 }= (a + b)^{2} - 2ab.

### How To Use the a^2 + b^2 Formula?

We have two a^{2} + b^{2} formulas and we need to choose the relevant formula depending upon the available information.

- a
^{2}+ b^{2 }= (a + b)^{2}- 2ab - a
^{2}+ b^{2 }= (a - b)^{2}+ 2ab

### What is the Difference Between a Square + b Square and a Square - b Square Formulas?

- a square plus b square formula is: a
^{2}+ b^{2 }= (a + b)^{2}- 2ab (or) (a - b)^{2}+ 2ab - a square minus b square formula is: a
^{2}- b^{2}= (a - b) (a + b)